Epigenetic Activation of Silent Biosynthetic Gene Clusters in Endophytic Fungi Using Small Molecular Modifiers - Pillay, Lynise C.; Nekati, Lucpah; Makhwitine, Phuti J.; Ndlovu, Sizwe I. (Frontiers in Microbiology, 2022)
The discovery of silent biosynthetic gene clusters (BGCs) in fungi provides unlimited prospects to harness the secondary metabolites encoded by gene clusters for various applications, including pharmaceuticals. Amplifying these prospects is the new interest in exploring fungi living in the extremes, such as those associated with plants (fungal endophytes). Fungal species in endosymbiosis relationship with plants are recognized as the future factories of clinically relevant agents since discovering that they can produce similar metabolites as their plant host. The endophytes produce these compounds in natural environments as a defense mechanism against pathogens that infect the plant host or as a strategy for mitigating competitors. The signaling cascades leading to the expression of silent biosynthetic gene clusters in the natural environment remain unknown. Lack of knowledge on regulatory circuits of biosynthetic gene clusters limits the ability to exploit them in the laboratory. They are often silent and require tailor-designed strategies for activation. Epigenetic modification using small molecular compounds that alter the chromatin network, leading to the changes in secondary metabolites profile, has achieved considerable success. This review aims to comprehensively analyze the secondary metabolite profiles expressed after treatment with various epigenetic modifiers. We first describe the regulatory circuits governing the expression of secondary metabolites in fungi. Following this, we provide a detailed review of the small molecular modifiers, their mechanism(s) of action, and the diverse chemistries resulting from epigenetic modification. We further show that genetic deletion or epigenetic inhibition of histone deacetylases does not always lead to the overexpression or induction of silent secondary metabolites. Instead, the response is more complex and often leads to differential expression of secondary metabolites. Finally, we propose using this strategy as an initial screening tool to dereplicate promising fungal species.